Research Trends in Family Psychology: from Disadvantage to Resilience - A.V. Makhnach (Социальная психология и общество)
A special issue of the journal "Social Psychology of the Modern Family" is devoted to the research of the modern family in the context of socio-psychological knowledge. The issue reflects trends, the general state and problems of family psychology, highlights a number of fundamental socio-psychological problems of the family that underlie its dynamic development in modern society, and identifies further research prospects in this area.